Investigation of the Impact of Hydrological and Thermal Stress on Germination Response to Identify Ecological Filters of Rarity and Endemism - Rajapakshe, Rajapakshe Pathirennehelage Villaddara Gamage Subhashi Wasanthi (Curtin University, 2021)
Thermal stress and water stress are two major environmental variables that affect seed germination, particularly in arid ecosystems. This study investigated the role of thermal stress and water stress in shaping the germination niche of a diverse group of plants endemic to rocky outcrop habitats of Western Australia, and quantified germination responses in terms of ecological and evolutionary implications.